Islamic civilization in thirty lives the first 1,000 years - Robinson, Chase F. (University of California Press, 2016)
Religious thinkers, political leaders, lawmakers, writers, and philosophers have shaped the 1,400-year-long development of the world's second-largest religion. But who were these people? What do we know of their lives and the ways in which they influenced their societies? In Islamic Civilization in Thirty Lives, the distinguished historian of Islam Chase F. Robinson draws on the long tradition in Muslim scholarship of commemorating in writing the biographies of notable figures, but he weaves these ambitious lives together to create a rich narrative of Islamic civilization, from the Prophet M.